Promoting Rigorous Research: Generalizability and Qualitative Research - Hays, Danica G.; McKibben, W. Bradley (Journal of counseling and development, 2021)
Although generalizability is not typically considered a feature or goal of qualitative research, it is an integral part of applying findings to advance knowledge in the counseling profession. First, we describe types of generalizability, the use of trustworthiness criteria, and strategies for maximizing generalizability within and across studies, then we discuss how the research approaches of grounded theory, autoethnography, content analysis, and metasynthesis can yield greater generalizability of findings. We then describe six phases for aggregating qualitative research to conduct a metasynthesis, which can be applied as relevant to the metastudy approaches of formal grounded theory, autoethnography, and content analysis.